Genetic Basis of Dorper Sheep (Ovis aries) Revealed by Long-Read De Novo Genome Assembly - Qiao, Guoyan; Xu, Pan; Guo, Tingting; Wu, Yi; Lu, Xiaofang; Zhang, Qingfeng; He, Xue; Zhu, Shaohua; Zhao, Hongchang; Lei, Zhihui; Sun, Weibo; Yang, Bohui; et al. (Frontiers in Genetics, 2022)
Dorper sheep (Ovis aries) (DPS), developed in the 1930s by crossing Dorset Horn and Blackhead Persian sheep in South Africa, is a world-famous composite breed for mutton production. The genetic basis underlying this breed is yet to be elucidated. Here, we report the sequencing and assembly of a highly contiguous Dorper sheep genome via integration of Oxford Nanopore Technology (ONT) sequencing and Hi-C (chromatin conformation capture) approaches. The assembled genome was around 2.64 Gb with a contig N50 of 74.13 Mb and 138 contigs in total. More than 99.5% of the assembled sequences could be anchored to 27 chromosomes and they were annotated with 20,450 protein-coding genes. Allele-specific expression (ASE) genes of Dorper sheep were revealed through ASE analysis and they were involved in the immune system, lipid metabolism, and environmental adaptation. A total of 5,701 and 456 allelic sites were observed in the SNP and indels loci identified from relevant whole-genome resequencing data. These allelic SNP and INDEL sites were annotated in 1,002 and 294 genes, respectively. Moreover, we calculated the number of variant sites and related genes derived from the maternal and paternal ancestors, revealing the genetic basis of outstanding phenotypic performance of Dorper sheep. In conclusion, this study reports the first reference genome of Dorper sheep and reveals its genetic basis through ASE. This study also provides a pipeline for mining genetic information of composite breeds, which has an implication for future hybrid-breeding practices.